2018
DOI: 10.1016/j.juro.2017.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Care Use among Patients with Spina Bifida: Change in Care from Childhood to Adulthood

Abstract: Purpose We examined the ambulatory health care visit utilization of spina bifida children, adults who transitioned to adult care, and adults who continued to seek care in a pediatric setting. Methods We evaluated utilization over a one-year period for SB patients who visited any outpatient medical clinic within an integrated health care system. Patients were categorized as pediatric (<18) or adult (≥ 18). Adults were divided into those who did not fully transition to adult care (DNT) and patients who fully t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…16 Lack of structured transition intervention is associated with adverse consequences, which include discontinuity of care, 17,18 difficulties with treatment adherence, 19 excess morbidity, 20 dissatisfaction and worry, 21 -23 and preventable emergency department and hospital visits. 24 The few studies on transition among youth without special health care needs (non-YSHCN) reveal they are less involved in completing medical tasks than peers with SHCNs. Additionally, HCPs are no more likely to discuss future goals with YSHCN than with non-YSHCN.…”
mentioning
confidence: 99%
“…16 Lack of structured transition intervention is associated with adverse consequences, which include discontinuity of care, 17,18 difficulties with treatment adherence, 19 excess morbidity, 20 dissatisfaction and worry, 21 -23 and preventable emergency department and hospital visits. 24 The few studies on transition among youth without special health care needs (non-YSHCN) reveal they are less involved in completing medical tasks than peers with SHCNs. Additionally, HCPs are no more likely to discuss future goals with YSHCN than with non-YSHCN.…”
mentioning
confidence: 99%
“…Shepard et al [27] investigated differences between two groups of young adults (18e25), one that transitioned to adult care and on that did not. They found that patients who had not transitioned had a significantly higher use of outpatient and emergency care.…”
Section: Effects Of Previous Clinical Modelsmentioning
confidence: 99%
“…When the transition to adult care has been established, the primary care provider might play the biggest role in the day to day needs of these patients with chronic care needs [2,23]. Based on regular assessments, general practitioners can navigate the patient through the multidisciplinary landscape and provide early referral when needed [3,27]. Given the rarity of these congenital urological anomalies and the rather recent advances in medicine, little is known about the natural course of these complex disorders in later life.…”
Section: Proposals For Improvement By Established Transitional Care Modelsmentioning
confidence: 99%
“…Seamlessly moving from pediatric to adult health care is a critical aspect of transitioning from childhood to adulthood for youth with special health care needs, and structured pediatric to adult care transition programs are associated with positive outcomes [6][7][8]. Without appropriate health care transition services, youths with special health care needs are vulnerable to adverse outcomes, such as loss of continuity of care [9,10], preventable morbidity, emergency department visits, and hospital visits [11,12]. Pediatric to adult health care transitions should be characterized by having an organizational policy in place that supports care transitions, developing tracking and monitoring processes that follow youths with special health care needs as they transition, assessing youth transition readiness, and transferring care [13].…”
Section: Introductionmentioning
confidence: 99%
“…Seamlessly moving from pediatric to adult health care is a critical aspect of transitioning from childhood to adulthood for youth with special health care needs, and structured pediatric to adult care transition programs are associated with positive outcomes [ 6 - 8 ]. Without appropriate health care transition services, youths with special health care needs are vulnerable to adverse outcomes, such as loss of continuity of care [ 9 , 10 ], preventable morbidity, emergency department visits, and hospital visits [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%